2020
DOI: 10.1093/jat/bkaa189
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Optical Hematocrit Measurement from Dried Blood Spots

Abstract: The impact of the hematocrit (HCT) on the dried blood spot (DBS)’s spreading area is one of the most important hurdles, which prevents the full acceptance of quantitative microsampling strategies. Several destructive and non-destructive strategies to assess the HCT from a DBS post-sampling have been presented. Unfortunately, the current methods are either labor-intensive, require a complicated algorithm or are not automatable. Here, we present a novel setup that permits the fully automated reflectance analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…This differs from the linear regression proposed by Luginbühl et al – however, that model was set up and evaluated using only a limited number of samples and relying on the correlation coefficient ( r 2 ), without in-depth validation, as performed here. 21 In addition, Capiau et al validated a linear regression model after log–log transformation. 15,16 Although these authors found the model to be statistically non-linear, a linear model was accepted based on the back-calculated values of the calibrators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This differs from the linear regression proposed by Luginbühl et al – however, that model was set up and evaluated using only a limited number of samples and relying on the correlation coefficient ( r 2 ), without in-depth validation, as performed here. 21 In addition, Capiau et al validated a linear regression model after log–log transformation. 15,16 Although these authors found the model to be statistically non-linear, a linear model was accepted based on the back-calculated values of the calibrators.…”
Section: Resultsmentioning
confidence: 99%
“…16 Overall, the method's performance was comparable to that of the previously published manual method, except for the precision, which was greatly improved, and with the substantial advantage that the fully automated set-up eliminates any hands-on time. 12,14–16,21…”
Section: Resultsmentioning
confidence: 99%
“…The use of DBS sampling in combination with DBS autosamplers overcomes some of the aforementioned challenges and permits fully automated analysis of PEth in combination with nondestructive HCT assessment and correction, using single‐wave reflectance spectroscopy, within about 5 min per sample (Luginbühl, Fischer, et al, 2020; Luginbühl, Gaugler, et al, 2019; Luginbühl, Stöth, et al, 2020). This represents a significant advantage, as large batches of samples can be processed in a fully automated manner, “from card to chromatogram, with no hands‐on.”…”
Section: Evolutionmentioning
confidence: 99%
“…In a joint effort between the University of Applied Sciences FHNW, the newborn screening laboratory of the children's Hospital Zürich and CAMAG, a new mass spectrometry-based screening method for amino acids, acylcarnitins, and steroids was developed and implemented (CTI Project: 16898.1 PFLS-LS). [5][6][7]…”
Section: Automated Dried Blood Spot Analysis For Newborn Screeningmentioning
confidence: 99%